Uczniowska konkretyzacja lektury pozaszkolnej i jej miejsce w literackiej świadomości młodzieży = Schoolboy's Substantiation of Extraschool Reading and its Place in the Literary Consciousness of Young People - Inglot, Mieczysław (1931- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the paper under the above title the author postulates to pay attention to the pupils' extraschool literary reading experiences. It is assumed that they form a weighty reference system for the consideration on the modernization of teaehing literature in school.
Keywords: dydaktyka literatury; młodzież; czytelnictwo